Lentivirus-mediated LIGHT overexpression inhibits human colorectal carcinoma cell growth in vitro and in vivo - WANG, HAIBO (D.A. Spandidos, 2013)
Human LIGHT (lymphotoxin-related inducible ligand that competes for glycoprotein D binding to herpesvirus entry mediator on T cells) is the 14th member of the tumor necrosis factor (TNF) superfamily and is therefore also known as TNFSF14. LIGHT has been proven to be a multifunctional molecule affecting cell proliferation, differentiation and a number of other biological processes, in particular, cell growth inhibition. However, the expression and molecular mechanisms of the LIGHT gene in human colorectal carcinoma cells remain largely unclear. In the present study, the LIGHT gene was overexpressed using a lentiviral expression vector in HCT116 human colorectal carcinoma cells in vitro and in vivo, in order to explore the mechanism by which the LIGHT gene inhibits cell growth and suppresses tumor formation. The results showed that the recombinant lentivirus with LIGHT overexpression inhibited the proliferative capacity of the HCT116 cells and significantly decreased the xenografted tumor volumes in nude mice. Furthermore, LIGHT treatment effectively initiated increased caspase-3 and decreased Bcl-2 activities in the HCT116 cells. This study provides a basis for the improved understanding of the role and molecular mechanisms of the LIGHT gene in human colorectal carcinoma cells and may facilitate further functional studies of LIGHT.